PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT PADA PEMBELAJARAN MATEMATIKA MATERI BENTUK ALJABAR DI SMP NEGERI 2 TONDANO - Apriyani, Rini; Domu, Ichdar; Sumarauw, Sylvia (Dharmas Education Journal (DE_Journal), 2024)
This research was motivated by students' lack of self-confidence in expressing opinions when studying algebra material and students' low interest in studying mathematics, especially algebra material because it was considered difficult, resulting in reduced attention to the teacher's explanations and as a result academic decline. So the researchers applied the TGT model with the aim of The main objective is to examine differences in average mathematics learning outcomes by applying the Teams Games Tournament (TGT) type cooperative learning model to learning algebra material. This research uses a quasi-experimental approach. Class VII students for the 2023–2024 academic year of SMP Negeri 2 Tondano participated in this research. Two classes were used as research samples: VII-B as the experimental group and VII-C as the control group. Each group consists of 24 students. Standardized assessments developed with the aim of measuring learned material are used as educational tools. The t value of 4.442 was calculated using the t test at a significance level of 0.05, while the critical t value was 1.684. We can reject the null hypothesis (Ho) because the calculated t_value is greater than the t_table value. This shows that on average students whose teachers apply the Teams Games Tournament (TGT) teaching model obtain better results in class than teachers whose students do not apply this model.